2021
DOI: 10.5194/acp-21-951-2021
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft-based inversions quantify the importance of wetlands and livestock for Upper Midwest methane emissions

Abstract: Abstract. We apply airborne measurements across three seasons (summer, winter and spring 2017–2018) in a multi-inversion framework to quantify methane emissions from the US Corn Belt and Upper Midwest, a key agricultural and wetland source region. Combing our seasonal results with prior fall values we find that wetlands are the largest regional methane source (32 %, 20 [16–23] Gg/d), while livestock (enteric/manure; 25 %, 15 [14–17] Gg/d) are the largest anthropogenic source. Natural gas/petroleum, waste/landf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 86 publications
4
29
0
Order By: Relevance
“…The highest emissions in the gridded version of the EPA (2016) GHGI are for the upper Midwest, and our inversion results suggest that these are too low, possibly reflecting higher-emitting manure management systems from confined animal feeding operations than included in the GHGI calculations (Sheng et al, 2018a). Yu et al (2021) also found from an aircraft-based inversion that livestock emissions from the EPA inventory over the US corn belt and upper Midwest region are underestimated by 25 % during summer and winter.…”
Section: Optimized 2010-2017 Anthropogenic Methane Emissions For Conus Canada and Mexicomentioning
confidence: 62%
See 1 more Smart Citation
“…The highest emissions in the gridded version of the EPA (2016) GHGI are for the upper Midwest, and our inversion results suggest that these are too low, possibly reflecting higher-emitting manure management systems from confined animal feeding operations than included in the GHGI calculations (Sheng et al, 2018a). Yu et al (2021) also found from an aircraft-based inversion that livestock emissions from the EPA inventory over the US corn belt and upper Midwest region are underestimated by 25 % during summer and winter.…”
Section: Optimized 2010-2017 Anthropogenic Methane Emissions For Conus Canada and Mexicomentioning
confidence: 62%
“…Methane emissions for the year 2012, from the 2016 version of this inventory (EPA, 2016), were spatially allocated on a 0.1 • × 0.1 • (10 × 10 km) grid by Maasakkers et al (2016) to enable its evaluation using top-down methods. Results using analysis of atmospheric methane measurements from ground, aircraft, and satellite platforms show larger methane emissions than reported in the GHGI, particularly for the oil and gas industry (Alvarez et al, 2018;Zhang et al, 2020;Lu et al, 2021;Qu et al, 2021) and for livestock (Lu et al, 2021;Yu et al, 2021). Atmospheric observations also suggest an increasing trend of US anthropogenic emissions over the past decade (Turner et al, 2016;Sheng et al, 2018a;Lan et al, 2019;, while the GHGI indicates a decrease (EPA, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, various atmospheric studies monitoring emissions from O&G from individual wellpads (Caulton et al, 2019;Rella et al, 2015;Robertson et al, 2017), basins (Barkley et al, 2017;Karion et al, 2013Karion et al, , 2015Peischl et al, 2015Peischl et al, , 2016Peischl et al, , 2018Pétron et al, 2012Pétron et al, , 2014, and entire regions have consistently found emission rates larger than the EPA inventory, raising concerns of a broad underestimation of leaks from the O&G sector (Alvarez et al, 2018). However, large-scale CH 4 inversion studies involving the US have not been as conclusive, with differing findings as to the accuracy of inventory emissions from O&G, animal agriculture, and wetlands (Maasakkers et al, 2019;Miller et al, 2013;Sheng et al, 2018;Yu et al, 2020). The large spread of uncertainty regarding the magnitude, spatial distribution, and seasonality of CH 4 emissions from wetlands, as well as the numerous other potential sources of CH 4 , poses a challenge to large scale studies attempting source attribution of detected CH 4 signals.…”
mentioning
confidence: 99%
“…The highest emissions in the gridded version of the EPA (2016) GHGI are for the Upper Midwest 535 and our inversion results suggest that these are too low, possibly reflecting higher-emitting manure management systems from confined animal feeding operations than included in the GHGI calculations (Sheng et al, 2018a). Yu et al (2021) also found from an aircraft-based inversion that livestock emissions from the EPA inventory over the US Corn Belt and Upper Midwest region are underestimated by 25% during summer and winter.…”
mentioning
confidence: 88%